Legal Aspects of Informed Consent in Medical Procedures - Anna Veronica Pont; Kevin Mario Immanuel; Natasya Yunita Sugiastuti; Zabidin; Stelvia W. Noya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Informed consent is a fundamental component of modern medical practice that emphasizes the importance of a patient’s approval after receiving clear, adequate, and understandable information regarding a medical procedure. This concept reflects not only respect for patient autonomy but also serves as a legal safeguard for healthcare professionals in the performance of their duties. In Indonesia, the regulation of informed consent has undergone notable development. Ministerial regulations, the Medical Code of Ethics, and Law No. 17 of 2023 on Health provide the normative foundation that affirms patients’ rights to obtain sufficient information and to give conscious consent before any medical intervention. This study applies a normative juridical method with a statutory and conceptual approach. The findings reveal that the latest legal framework reinforces documentation obligations and clarifies the standards that must be fulfilled by medical practitioners, including in emergency situations. Nevertheless, practical implementation remains challenged by several factors, such as patients’ limited comprehension, the use of complex medical terminology, time constraints faced by healthcare providers, and the suboptimal practice of written documentation. These challenges create potential legal disputes, both in civil and criminal domains, when medical procedures are carried out without valid consent. Therefore, the effective application of informed consent requires synergy between clear regulations, adequate understanding among medical personnel, and improved health literacy among the public. Consequently, informed consent should not be seen merely as an administrative formality but rather as an essential legal and ethical safeguard that enhances the quality of healthcare services.